The Effect of Green Accounting Disclosure on the Firm Value of Listed Mining and Agriculture Companies in Southeast Asia Countries - Fernando, Kenny; Jocelyn, Han; Frista, Frista; Kurniawan, Budi (International Journal of Energy Economics and Policy, 2024)
The purpose of the study is to seek how Green Accounting Disclosure (GAD) affects firm value using GDA Coverage Percentage quantified by NVIVO Software in Mining and Agriculture Companies in Southeast Asia. The five-year observation period for this study taken from 2017 to 2021. This research uses control variables, such as profitability, sales growth, leverage and size of mining and agriculture company in Southeast Asia. The data used were secondary data obtained from Capital IQ SnP and annual reports and/or sustainability reports posted on the company websites. Data regression with a fixed effect model approach was used for data analysis. The findings indicate that Green Accounting Disclosure, as reflected by coverage percentage in compliance with GRI standard, has insignificant on firm value in Mining and Agriculture Companies. Leverage is the only variable that matters on GAD. Even though GAD performed by this study is more rigid than binary variable, The keywords need to be developed to quantify what it takes in determining GAD variable. Though green accounting disclosure is not associated with the firm value, the author’s additional analysis found that there are only a few companies in Southeast Asia that disclose green accounting in their report. Since the disclosure of green accounting is voluntarily and companies are still hesitant to voluntarily disclose green accounting in their reports.